Effect of Florasulam and 2,4-D on Fineleaf Fumitory (Fumaria parviflora Lam.) Infestation in Wheat Crop - B. Hajjaj; A. El Oualkadi; H. Tantaoui; M. Chentouf (Archives of Current Research International, 2019)
Aims: High infestations of Fumaria parviflora (Fineleaf fumitory) may led to cereal crops yield reduction. The aim of this study is to investigate the effect of mixture of Florasulam and 2,4-D on F. parviflora infestation in a soft wheat crop. Study Design: The experimental design was Randomized Complete Block Design (RCBD) with three replications. Each block contained 4 elementary plots, 3 plots of which were treated with three rates of application of mixture of Florasulam and 2.4-D and one untreated control plot. Place and Duration of Study: Trials were conducted in Ouazzane region of Morocco in January 2017. Calculation of dry F. parviflora biomass was carried out at weed research laboratory of INRA-CRRA Tangier in March 2017. Methodology: Treatments were carried out with a knapsack sprayer with the nozzle delivering a 3 bar jet. A quadrant of 1 m x 1 m was used to calculate percentage of F. parviflora density reduction, height reduction and biomass reduction. F. parviflora dry biomass were determined using an oven at 75ºC for 48 hours. Then, weighed with a precision balance. Results: Treatment with mixture of Florasulam and 2,4-D respectively at 5.63 and 270 g/ha gave the best control of F. parviflora infestations. In fact, “Florasulam+2,4-D” at (5.63+270) g/ha recorded 85±3.1%, 81±2.5% and 92±3.1% respectively on F. parviflora density reduction, F. parviflora height reduction and F. parviflora dry biomass reduction. “Florasulam+2,4-D” at (3.75 +180) g/ha recorded 66±5.3%, 63±4.7% and 74±2.6% respectively on F. parviflora density reduction, F. parviflora height reduction and F. parviflora dry biomass reduction. Florasulam + 2,4-D at (1.88+90) g/ha recorded the lowest efficacies 45±10.4%, 22±9.5% and 45±11.4% respectively on F. parviflora density reduction, F. parviflora height reduction and F. parviflora dry biomass reduction. Conclusion: «Florasulam+2,4-D» at (5.63+270) g/ha could be recommended to farmers in Ouazzane region when F. parviflora infestation is dominant on wheat. A further assessment of «Florasulam+2,4-D» residues in soils and their phytotoxicities should be evaluated on other crops grown in rotations.